Issues for designing a flexible expressive audiovisual system for real-time performance & composition (2004)
This paper begins by evaluating various systems in terms of factors for building interactive audiovisual environments. The main issues for flexibility and expressiveness in the generation of dynamic sounds and images are then isolated. The design and development of an audiovisual system prototype is described at the end.